2008
DOI: 10.1111/j.1745-6584.2008.00415.x
|View full text |Cite
|
Sign up to set email alerts
|

Electrokinetic Migration of Permanganate Through Low‐Permeability Media

Abstract: This research was conducted to evaluate the combination of electromigration and potassium permanganate as a potential remediation method for low-permeability media (e.g., soil and sediment) contaminated with dissolved and sorbed organic contaminants. The experimental procedure was composed of two stages: determination of migration rates of permanganate through homogeneous cores and a primarily qualitative analysis of migration in more heterogeneous, two-dimensional scenarios. Results indicated that transport o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(31 citation statements)
references
References 10 publications
0
31
0
Order By: Relevance
“…If multiple wells/rods are installed, the temporary well injection method could be completed as a multiple well injection array, further increasing flexibility in operations. Pore dilation—the use of proprietary injection equipment designed to use pressure waves to temporarily dilate the intergranular/fracture pore throats, facilitating increased rates of injection and more homogeneous distribution. Recirculation—the use of recirculation zones within an aquifer where injectate distribution can be closely controlled. These mixing zones may be completed in vertical zones (in thicker aquifers) or in horizontal zones (injectate flood). Electrokinetics—the use of impressed electric potential to move charged particles (of permanganate, for example) in the subsurface (Reynolds et al., ) at rates greater than advection or diffusion. Electrokinetic approaches thus far have remained limited for large‐scale mainstream remediation. Soil heating—use of various forms of thermal energy (e.g., heat, steam, electrical current, and microwave) to heat the target soils.…”
Section: Delivery Methods Toolboxmentioning
confidence: 99%
“…If multiple wells/rods are installed, the temporary well injection method could be completed as a multiple well injection array, further increasing flexibility in operations. Pore dilation—the use of proprietary injection equipment designed to use pressure waves to temporarily dilate the intergranular/fracture pore throats, facilitating increased rates of injection and more homogeneous distribution. Recirculation—the use of recirculation zones within an aquifer where injectate distribution can be closely controlled. These mixing zones may be completed in vertical zones (in thicker aquifers) or in horizontal zones (injectate flood). Electrokinetics—the use of impressed electric potential to move charged particles (of permanganate, for example) in the subsurface (Reynolds et al., ) at rates greater than advection or diffusion. Electrokinetic approaches thus far have remained limited for large‐scale mainstream remediation. Soil heating—use of various forms of thermal energy (e.g., heat, steam, electrical current, and microwave) to heat the target soils.…”
Section: Delivery Methods Toolboxmentioning
confidence: 99%
“…Although EK approaches have been applied for decades to enhance contaminant migration, recent work shows the technology offers new promise if applied to deliver remediation reagents into low‐permeability zones and increase overall reagent distribution uniformity in geologically heterogeneous settings. A number of recent laboratory studies have demonstrated the potential for EK techniques to enhance the delivery of permanganate (Reynolds et al ), lactate and bacteria (Mao et al ), and surfactants (e.g., Hahladakis et al ). More specifically, in laboratory experiments, Mao et al () were able to distribute Dehalococcoides and lactate ions at transport rates of approximately 3.2 cm/day across a bentonite clay, resulting in the complete dechlorination of PCE.…”
Section: Electrokinetic‐enhanced Reagent Deliverymentioning
confidence: 99%
“…Although EK approaches have been applied for decades to enhance contaminant migration, recent work shows the technology offers new promise if applied to deliver remediation reagents into low-permeability zones and increase overall reagent distribution uniformity in geologically heterogeneous settings. A number of recent laboratory studies have demonstrated the potential for EK techniques to enhance the delivery of permanganate (Reynolds et al 2008), lactate and bacteria (Mao et al 2012), and surfactants (e.g., Hahladakis et al 2016). More specifically, in laboratory experiments, Mao et al (2012) were able to distribute Dehalococcoides and lactate ions at transport rates of approximately 3.2 cm/day across a bentonite clay, resulting in the complete dechlorination of PCE.…”
Section: Electrokinetic-enhanced Reagent Deliverymentioning
confidence: 99%